Evidence‐based treatment recommendations for neck and low back pain across Europe: A systematic review of guidelines - Corp, Nadia (Eur J Pain, 2020)
BACKGROUND AND OBJECTIVE: This systematic review synthesized evidence from European neck and low back pain (NLBP) clinical practice guidelines (CPGs) to identify recommended treatment options for use across Europe. DATABASES AND DATA TREATMENT: Comprehensive searches of thirteen databases were conducted, from 1st January 2013 to 4th May 2020 to identify up‐to‐date evidence‐based European CPGs for primary care management of NLBP, issued by professional bodies/organizations. Data extracted included; aim and target population, methods for development and implementation and treatment recommendations. The AGREE II checklist was used to critically appraise guidelines. Criteria were devised to summarize and synthesize the direction and strength of recommendations across guidelines. RESULTS: Seventeen CPGs (11 low back; 5 neck; 1 both) from eight European countries were identified, of which seven were high quality. For neck pain, there were consistent weak or moderate strength recommendations for: reassurance, advice and education, manual therapy, referral for exercise therapy/programme, oral analgesics and topical medications, plus psychological therapies or multidisciplinary treatment for specific subgroups. Notable recommendation differences between back and neck pain included, i) analgesics for neck pain (not for back pain); ii) options for back pain‐specific subgroups—work‐based interventions, return to work advice/programmes and surgical interventions (but not for neck pain) and iii) a greater strength of recommendations (generally moderate or strong) for back pain than those for neck pain. CONCLUSIONS: This review of European CPGs identified a range of mainly non‐pharmacological recommended treatment options for NLBP that have broad consensus for use across Europe. SIGNIFICANCE: Consensus regarding evidence‐based treatment recommendations for patients with neck and low back pain (NLBP) from recent European clinical practice guidelines identifies a wide range of predominantly non‐pharmacological treatment options. This includes options potentially applicable to all patients with NLBP and those applicable to only specific patient subgroups. Future work within our Back‐UP research team will transfer these evidence‐based treatment options to an accessible clinician decision support tool for first contact clinicians.